Touristic Destinations’ Perceived Risk And Perceived Value As Indicators Of E-Wom And Revisit Intentions - Uslu, Abdullah; Karabulut, Ali Naci (International Journal of Contemporary Economics and Administrative Sciences, 2018)
In the process of destination selection, it is known that tourists perceive many different risks and use eWOM behavior as a risk reduction tool. Also the risks that consumers perceive are influential on the values they perceive. For this reason, spreading positive eWOM messages and encouraging revisit intentions are seen as significant competitive advantages in terms of destination management. In this context, to measure the effects of tourists’ perceived risk on their perceived value and the effects of their perceived value on their eWOM dissemination and revisit intentions, have been identified as the main objectives of this study. The sample of the study consists 228 tourists who visited the Fethiye (TR) destination in 2017. As a result of analysis of the data with Structural Equation Modeling, it is found that perceived risk variable has an impact on perceived value, perceived value variable has impacts on eWOM dissemination intention and revisit intention and eWOM dissemination intention has an impact on revisit intention.